Faktor Penyebab Pembangunan Insfrastruktur Untuk Pelayanan Publik Yang Masih Terbatas Didaerah Perbatasan - Kalistus Gudensius Wayong Huler; Yohanes Arman; Allesandro Patricio Quinaldy Ragat (Pusat Riset dan Inovasi Nasional, 2023)
The border is an important aspect of the state because it determines the area of ​​authority and sovereignty of the state which intersects with the sovereignty of other countries. The border is also a very strategic area for a country, because it involves socio-cultural, economic, political, defense and security aspects. Based on Law No. 43 of 2008 concerning state territory, states that the border area is part of the country's territory which is located on the side along the border of Indonesia's territory with other countries and the border area is in the sub-district. The Law on State Territories also explains that the development of Indonesia's border areas is the responsibility of the state. Development in the field of infrastructure is also a major supporting factor for the main functions of the social system and economic system, such as the availability of health facilities, roads, air transportation, markets and educational facilities which support people's daily lives. With an infrastructure system that supports the community to move dynamically and makes it easier for the community to carry out economic activities, investors can invest in the regions. So that isolated/hard-to-reach areas can be accessed easily.